2023
DOI: 10.1039/d3se00369h
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical nitrogen reduction to ammonia using mesoporous iron oxide with abundant oxygen vacancies

Abstract: The electrochemical nitrogen reduction reaction (NRR) has emerged as an environmentally benign and sustainable approach for ammonia (NH3) synthesis. For the development of an efficient NRR electrocatalyst, herein, mesoporous hematite...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…–1 and 16.4%, respectively. This optimum performance of Cu–Fe 2 O 3 -1 is comparable to or even exceeds those of recently reported Fe oxide-based electrocatalysts, , , , and the marked FE is higher than that of Zn-doped Fe 2 O 3 , as expected in the Introduction. Upon shifting the applied potential in a negative direction beyond −0.20 V, both NH 3 formation rate and FE gradually decreased because of the competing HER process (Figure S14), whereas the smaller FE observed at −0.10 V is likely due to uncontrollable experimental error and the capacitance of the carbon support. , The durability of Cu–Fe 2 O 3 -1 was evaluated by conducting a consecutive cycling test and a long-term chronoamperometry measurement.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…–1 and 16.4%, respectively. This optimum performance of Cu–Fe 2 O 3 -1 is comparable to or even exceeds those of recently reported Fe oxide-based electrocatalysts, , , , and the marked FE is higher than that of Zn-doped Fe 2 O 3 , as expected in the Introduction. Upon shifting the applied potential in a negative direction beyond −0.20 V, both NH 3 formation rate and FE gradually decreased because of the competing HER process (Figure S14), whereas the smaller FE observed at −0.10 V is likely due to uncontrollable experimental error and the capacitance of the carbon support. , The durability of Cu–Fe 2 O 3 -1 was evaluated by conducting a consecutive cycling test and a long-term chronoamperometry measurement.…”
Section: Resultssupporting
confidence: 83%
“…Furthermore, our group developed O V -enriched mesoporous Fe 2 O 3 and revealed that O V s promote N 2 activation (15.3 μg h –1 mg cat. –1 , 13.2%) from both experimental and computational results …”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Up to now, a series of characterization methods have been used for quantitative characterizations for NH 3 yield, such as the colorimetric method (indophenol blue method, [9,19,84] the phenate method, [85] and Nessler's reagent method [86] ), 1 H nuclear magnetic resonance (NMR), [9] ammonia-ion selective electrode (ASE) method, [15] and ion chromatography (IC), [15] and so on.…”
Section: Quantitative Characterization Of Nhmentioning
confidence: 99%